La Incongruencia, Juridica, En La Ley Contra La Violencia A La Mujer Y La Familia, Afecta Gravemente A La Dignidad Y Seguridad Juridica Social, De La Pareja Y De Mas Miembros Del Nucleo Familiar Art 1, 13.Lit.1,2,3,4,5 Y 20 Del Reglamento General , En La Necesidad De Reformar . - Chicaiza Orozco, Luis Fernando (2016)
The family as the fundamental unit of society, is an institution that must provide protection and affection, but unfortunately in some cases, the family, is being structured through practices of domination, which backed by laws, leads to family breakdown, which mainly affects the couple and other family members. The member of the family nucleus, which in most cases women are mothers, they denounce certain cases of irregularities that violate his honor, integrity, and so forth trusting and flocking to the Law on Violence against Women and the family, in that it will solve some or most of their problems, but this law insufficient and does not lead to true paths of solution, Adding to this problematic Social Legal ignorance of the law, by both parties when constitutional rights, not only women but also men. The law further lacks a proper legal terminology, which entails making fair use of the rights, to save the women, that harm or exclude the rights of men as human beings, when these, in certain cases are suppressed and until frightened by misuse of parking tickets Rescue and protection on the part of a woman or a family member, and up to a lot of the times unjustly removed from their homes, without even thinking about the safeguards that as individuals and human beings, leaving aside the real meaning of justice. Since law 103 in its article 13. He notes that the authorities, when in any way to reach your knowledge a case of domestic violence, shall immediately to impose one or more of the measures of amparo, using the legal text, without thinking of the consequences of family breakdown that this entails. In the literal 1 of article 13 of Law 103, clearly manifests itself that gives relief ballots and that may be necessary looking to women and apart from the other members of the family, thereby restricting of powers and exaggerated defense, which leads to the misuse of the measures. I believe that the law 103 violence against women and the family, in regard to measures of Amparo, needed to be reformed because it does not seeks paths or true methods of solution of family integration of the couple or any member of the family affected, but rather to the conflictual disintegration of the family.